Identification and Validation of a Novel Immune-Related Four-lncRNA Signature for Lung Adenocarcinoma - Wang, Jixin; Yin, Xiangjun; Zhang, Yin-Qiang; Ji, Xuming (Frontiers in Genetics, 2021)
Lung adenocarcinoma is a major subtype of lung cancer, the prognosis of patients with which is associated with both lncRNAs and cancer immunity. In this study, we collected gene expression data of 585 LUAD patients from TCGA database and 605 subjects from GEO database. LUAD patients were divided into high and low immune cells infiltrated groups according to ssgsea algorithm to identify DEGs. Based on the 49 immune-related DE lncRNAs, a 4-lncRNA prognostic signature was constructed by applying LASSO regression, univariate Cox regression and stepwise multivariate Cox regression in sequence. Kaplan-Meier curve, ROC analysis and the testing GEO data sets verified the effectiveness of the signature in predicting OS. Univariate Cox regression and multivariate Cox regression suggested that the signature was an independent prognostic factor. The correlation analysis revealed that the infiltration immune cell subtypes was related to these lncRNAs.